EFFECT OF COPPER PROTEINATE INCLUSION IN FOOD ON GROWTH PERFORMANCE, CARCASS TRAITS AND MEAT QUALITY OF FINISHING PIGS - B. M. Colin-Alvarez; I. A. Domínguez-Vara; J. L. Bórquez-Gastelum; J. A. Partida-De la Peña; J. E. Sánchez-Torres; E. Morales-Almaraz; D. Trujillo-Gutierrez (Tropical and Subtropical Agroecosystems, 2019)
The objective was to evaluate the effect of including 0, 75, 150 and 225 mg Cu kg-1 MS of copper proteinate (P-Cu) in the feed on growth, carcass characteristics and meat quality of pigs for market. Twenty four pigs (12 females and 12 males) were used, initial weight 60.3±0.55 kg, fed with basal diet (BD) during 46 days, distributed in a completely randomized design, factorial 4x2 (levels of P-Cu and sex): T1=DB (0 mg of P-Cu kg-1 MS), T2=DB+75 mg of P-Cu, T3=DB+150 mg of P-Cu and T4=DB+225 mg of P-Cu. The dose of 225 mg of P-Cu increased the daily weight gain (DWG) and the feed efficiency (FE) (P<0.05). The P-Cu increased the area of chop (CHA) in females and reduced the back fat (BF) in males (P<0.05). The P-Cu increased (12.6%) the yield of primary cuts (YPC) (P<0.05). In treatments 3 and 4 the water loss was reduced 58.5 and 82.2% (P<0.05). The P-Cu affected (P<0.01) the final pH and the a* index (P<0.05) of the Longissimus thoracis muscle. In conclusion, the P-Cu improved the DWG, the FE, the CHA and the YPC, and reduced the BF in the carcass.